A new stent with streamlined cross-section can suppress monocyte cell adhesion in the flow disturbance zones of the endovascular stent. Issue 1 (2nd January 2016) - Chen, Zengsheng; Zhan, Fan; Ding, Jun; Zhang, Xiwen; Deng, Xiaoyan
Abstract : We proposed a new stent with streamlined cross-sectional wires, which is different from the clinical coronary stents with square or round cross-sections. We believe the new stent might have better hemodynamic performance than the clinical metal stents. To test the hypothesis, we designed an experimental study to compare the performance of the new stent with the clinical stents in terms of monocyte (U-937 cells) adhesion. The results showed that when compared with the clinical stents, the adhesion of U-937 cells were much less in the new stent. The results also showed that, when Reynolds number increased from 180 (the rest condition for the coronary arteries) to 360 (the strenuous exercise condition for the coronary arteries), the flow disturbance zones in the clinical stents became larger, while they became smaller with the new stent. The present experimental study therefore suggests that the optimization of the cross-sectional shape of stent wires ought to be taken into consideration in the design of endovascular stents.